PRIVATE MILITARY COMPANIES: LEGAL ASPECTS OF APPLICATION - Azamat M. Shadzhe; Eduard M. Afamgotov; Inna N. Gaidareva (Russian Studies in Law and Politics)
Article is devoted to the problems of development of private military companies in Russia. It shows the practice of private military companies in the current political situation in the world. The phenomenon of private military companies (PMCs) is a rather controversial and ambiguous topic. Over the past more than thirty years, PMCs have played an increasingly important role in local wars and regional conflicts. With further globalization of the world economy, the role of PMCs in future wars and armed conflicts will be increasing. The authors study international documents regulating the activities of these organizations. They point out the necessity of adopting a law to allow this type of activity on the territory of the Russian Federation. Private military companies actually exist within the country and their legalization would allow to introduce their activities into the legal field. Private military companies influence the sphere of human rights, is connected with corruption and dishonest performance of obligations in implementation of contracts. The penalties for establishing and participating in illegal armed groups are shown. The possibilities of their application, both in Russia and abroad, are highlighted.